Battle in the backyard - Wiseman, Daniel (New York : HarperAlley, 2023)
Marco makes the BEST sandwiches in the entire world! When he wants to chow down after school, he's got all the ingredients he needs: Mom's fresh baked hoagie roll, three slices of bologna, cheddar cheese, crispy lettuce, and the most important ingredient of all: special sauce! But something super strange is afoot when--out of nowhere--Marco's sandwich begins to talk... Turns out, Marco's miraculous meal might be his best friend ever! The two quickly bond over sweet tunes and stinky cheese, but will a squad of breakdancing squirrels bring an end to this friendship before it truly begins?
Ages 6-10
Grades 2-3
Keywords: Sandwiches -- Comic books, strips, etc; Squirrels -- Comic books, strips, etc; Break dancing -- Comic books, strips, etc; Comics (Graphic works); Graphic novels